OPTIMIZATION OF THE ROLES OF STAKEHOLDERS IN THE DEVELOPMENT OF SAMARES ECOTOURISM IN BIAK NUMFOR REGENCY - Gunardi Hamdani Hakim; Tutut Sunarminto; Nyoto Santoso (Media Konservasi, 2020)
Samares is a coastal area in the villages of Sepse and Imndi in the East Biak District, Papua. Samares has several natural tourism objects that have the potential to be used for ecotourism activities. However, the current condition of the potency for ecotourism has not been well developed. Stakeholders participation was analyzed to identify and map the stakeholders’ involvement and to formulate the role of stakeholders in the development of ecotourism in Samares. This research was conducted in Sepse Village from June to August 2019. Data were obtained from field observations, literature review, questionnaires and semi-directive interview. The data were analyzed using scoring technique to determine interest and influence of stakeholders. The results showed that there were 16 stakeholders involved in the development of ecotourism in Samares, which were categorized as subjects, key players, context setters, and crowds. Stakeholders consist of provincial and district government, NGO, community, and private entities. To enhance the development of ecotourism in Samares, increased collaboration of programs, synchronization and coordination that ecotourism management can be conducted unitedly and efficiently, increase stakeholders’ participation, and increasing tourism promotion activities in Samares. Keywords: cooperation, ecotourism, optimization, Samares, stakeholders’ role.